Stator Inter-Turn Short Circuit Fault Estimation for a DFIG-based Wind Turbine - Sayahi, Yosra; Allouche, Moez; Gamgui, Mariem; Moreau, Sandrine; Mehdi, Driss (Engineering, Technology & Applied Science Research, 2025)
This paper presents an Inter-Turn Short-Circuit (ITSC) fault detection and isolation method based on the Proportional-Integral observer (PIO) design. ITSC fault is one of the most common electrical faults in electrical machines, the early detection of which can significantly reduce maintenance costs and prevent wind turbine damage. Therefore, a fault detection and isolation method is proposed to evaluate the ITSC fault level affecting the stator windings of a Double-Fed Induction Generator (DFIG). First, a state-space model of the generator with an ITSC fault in the d-q reference frame is introduced. Based on this fault model, an unknown input observer described by a Takagi-Sugeno (TS) model is also used to detect and isolate the ITSC fault. This observer provides a good estimation of the unknown inputs despite the abrupt changes in wind speed and parameter variations in the DFIG. Finally, the effectiveness of the proposed ITSC fault estimation is highlighted through simulation on a 3-kW wind turbine system.